2014
DOI: 10.4271/2014-01-0604
|View full text |Cite
|
Sign up to set email alerts
|

The Aerodynamics of a Small Car Overtaking a Truck

Abstract: A more ambitious dynamic experiment was undertaken by Brown and Seeman,[6], using models catapulted along parallel tracks and passing a crosswind generator. Spacing between vehicles and relative velocities, including vehicles passing in opposite directions could be represented. The shape of the ABSTRACT The influence of a large truck on the aerodynamics of a small passenger car in an overtaking manoeuvre on the motorway was considered, many years ago, during the 1970's, to be a potential problem for the vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…The drag increased when the truck model was near the rear end of the vehicle model. This trend qualitatively agrees with the previous researches using the five times longer truck (Howell et al, 2014) and the same size vehicle (Noger et al, 2005) as the passing vehicle. Then, the trend of C D base at each relative position qualitatively agrees with this general trend of C D .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The drag increased when the truck model was near the rear end of the vehicle model. This trend qualitatively agrees with the previous researches using the five times longer truck (Howell et al, 2014) and the same size vehicle (Noger et al, 2005) as the passing vehicle. Then, the trend of C D base at each relative position qualitatively agrees with this general trend of C D .…”
Section: Resultssupporting
confidence: 93%
“…Many studies have explored the components of the flow field that likely affect aerodynamic stability, including the pressure field of the passing vehicle (Howell et al, 2014;Noger et al, 2005;Uystepruyst and Krajnović, 2013), the crosswind from the passing vehicle (Gilliéron, 2003;Howell et al, 2014), and other factors (e.g., the Venturi effect at the narrow gap between the two vehicles; Clarke, 2007;Yamamoto et al, 1997). To systematically summarize the contribution to the drag change in consideration of these components, we used the following procedure.…”
Section: Analytical Procedures Of Flow Phenomena Correlated With the Dmentioning
confidence: 99%
“…In the wind tunnel experiments, the quasi-steady overtaking experiments revealed that the loads increased under cross winds when the overtaking car was on the lee side of the overtaken vehicle. 2,3 The study by Noger and Van Grevenynghe 4 researched the transient aerodynamic force responses associated with quasi-steady aerodynamic loads acting on the overtaken vehicle when a heavy truck and a light vehicle are in the overtaking maneuver. In addition, the unsteady overtaking experiments were researched.…”
Section: Introductionmentioning
confidence: 99%
“…A car-truck overtaking wind tunnel test indicated that the pressure field around CONTACT Yiping Wang wangyiping@whut.edu.cn the front of a truck greatly influences the forces experienced by the overtaking car, and the influence is mainly dependent on the truck velocity. The dynamic changes in the side force and the yaw moment are also important concerns (Howell et al, 2014;Noger & Grevenynghe, 2011). A further wind tunnel test also revealed the influence of velocity ratio between the two overtaking vehicles on their aerodynamic performance (Telionis et al, 1984;Yamamoto et al, 1997).…”
Section: Introductionmentioning
confidence: 97%